2000
DOI: 10.1046/j.1365-2346.2000.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and serum procalcitonin levels following oesophagectomy

Abstract: Fig. 2. The progress of serum PCT levels from arrival on the ICU (T 0 ) to T 72 h postoperatively. Data are presented as minimum, maximum, 25±75% percentile and median. For statistical analysis Wilcoxon's test was used, **P < 0.001 vs. T 0 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
6
13
3
Order By: Relevance
“…2 The significantly higher PCT levels in the non-survivor group may be the result of a clinically undetectable bacterial translocation during 1082 CANADIAN JOURNAL OF ANESTHESIA FIGURE The progress of serum procalcitnonin (PCT) levels from arrival on intensive care unit (t 0 ) to 72 hr (t 72 ) postoperatively in survivors and non-survivors. Data are presented as boxes and whisker plots.…”
Section: Procalcitonin Levels Do Not Predict Mortality Following Majomentioning
confidence: 99%
See 1 more Smart Citation
“…2 The significantly higher PCT levels in the non-survivor group may be the result of a clinically undetectable bacterial translocation during 1082 CANADIAN JOURNAL OF ANESTHESIA FIGURE The progress of serum procalcitnonin (PCT) levels from arrival on intensive care unit (t 0 ) to 72 hr (t 72 ) postoperatively in survivors and non-survivors. Data are presented as boxes and whisker plots.…”
Section: Procalcitonin Levels Do Not Predict Mortality Following Majomentioning
confidence: 99%
“…Anesthesia with propofol and remifentanil has been reported in elective surgery and well prepared myasthenic patients. 2 An 80-yr-old male myasthenic patient (stage IIb Ossermann), with a previous history of prolonged neuromuscular blockade after anesthesia, was scheduled for emergency surgery for gangrenous perforated cholecystitis with peritonitis. Considering the patient's critical condition, the surgeons suggested a laparoscopic technique.…”
Section: Propofol and Remifentanil Without Muscle Relaxants In A Patimentioning
confidence: 99%
“…Our preliminary studies showed a mean PCT at 24 h postoperatively of 5.3±4.3 ng/ml -1 [22]. In a previous descriptive study we found that PCT >2.8 ng/ml -1 showed an 84% sensitivity of predicting mortality [12].…”
Section: Statisticsmentioning
confidence: 76%
“…Unfortunately, real pre-treatment of septic patients cannot be achieved in clinical practice. However, we found that major abdominal surgery, which carries a considerable risk of morbidity and mortality, initiates an inflammatory response as detected by increased PCT, CRP and M:Cr [22]. Therefore, we decided to pre-treat highrisk patients undergoing elective surgery with shortterm NAC infusion and assess its effect on the early postoperative course of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation